Bulletin catalog : 1939 through 1973. - Socialist Workers Party (SWP) (New York : SWP, 1974)
Bevat overzicht van volgende periodieken: International Information and Discussion Bulletins, International Internal Discussion Bulletins, The Party Builder, Education for Socialists Bulletins
Engels
Brochure